2009
DOI: 10.1051/0004-6361/200809494
|View full text |Cite
|
Sign up to set email alerts
|

The $\Sigma-{\sf \textit D}$ relation for planetary nebulae

Abstract: We present an extended analysis of the relation between radio surface brightness and diameter -the so-called Σ − D relation for planetary nebulae (PNe). We revise our previous derivation of the theoretical Σ − D relation for the evolution of bremsstrahlung surface brightness in order to include the influence of the fast wind from the central star. Different theoretical forms are derived:for the first and second phases of evolution and Σ ∝ D −3 for the final stage of evolution. Also, we analyzed several differe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 32 publications
3
10
0
Order By: Relevance
“…For larger values of slope, the sensitivity effect should force the measured slope to be little more than 2. Our measured value of β is expected to be subject to the flattening effect, however, we measure a β = 2.7 ± 0.4 which is consistent with the Galactic data analysed by Urošević et al (2009).…”
Section: σ − D Relation For Smc Pnesupporting
confidence: 88%
See 3 more Smart Citations
“…For larger values of slope, the sensitivity effect should force the measured slope to be little more than 2. Our measured value of β is expected to be subject to the flattening effect, however, we measure a β = 2.7 ± 0.4 which is consistent with the Galactic data analysed by Urošević et al (2009).…”
Section: σ − D Relation For Smc Pnesupporting
confidence: 88%
“…Our examination indicates that they are actually PN mimics. The exclusion of the identified mimics results in the excellent agreement with the Galactic measurements that Urošević et al (2009) reported.…”
Section: σ − D Relation For Smc Pnesupporting
confidence: 82%
See 2 more Smart Citations
“…Here we calibrate radio surface brightness to diameter (Σ − D) relation. Urošević et al (2009) derived theoretical Σ − D in the common power law form using the interacting stellar winds model (Zhang & Kwok 1993;Kwok 1994). Σ = S/Ω and D = θ d, where S is the source flux density, Ω is source occupied solid angle, θ is the source angular radius and d is the distance to the source.…”
Section: Descriptionmentioning
confidence: 99%